The prevalence of sepsis-induced coagulopathy in patients with sepsis: a secondary analysis of two german multicenter randomized controlled trials - Schmoch, Thomas; Möhnle, Patrick; Weigand, Markus A.; Briegel, Josef; Bauer, Michael; Bloos, Frank; Meybohm, Patrick; Keh, Didier; Löffler, Markus; Elke, Gunnar; Brenner, Thorsten; Bogatsch, Holger (Annals of intensive care, 2023)
Sepsis and septic shock are frequently accompanied by coagulopathy. Since the sepsis-induced coagulopathy (SIC) score was first described, subsequent studies from Asia revealed a SIC prevalence of 40-60%. In Europe, however, SIC prevalence in patients fulfilling sepsis criteria according to the third international consensus definition (SEPSIS-3) has not yet been evaluated.